NK/T-cell lymphoma with rash and peripheral neuropathy as the first manifestation: a case report and literature review - Zizhu Tian; Jing Tian; Jiafen Liao (Diagnostic Pathology, 2023)
Abstract Background Extranodal NK/T-cell lymphoma, nasal type (ENKTCL-NT), is a rare, aggressive subtype of non-Hodgkin lymphoma, and it usually presents as a destructive sinus mass that may attend epistaxis. However, ENKTCL-NT with the manifestation of peripheral neuropathy is pretty unusual. Case presentation A 17-year-old Chinese patient presented with peripheral neuropathy and positive auto-antibodies. However, she failed methylprednisolone pulse therapy and developed hemophagocytic syndrome. The diagnosis of CD30-positive primary cutaneous ENKTCL-NT was confirmed by pathological biopsy. Her disease was brought under control after five cycles of chemotherapy. Conclusions The report findings are helpful in the differential diagnosis of peripheral neuropathy and autoimmune disease. We should be alert for the development of ENKTCL-NT when the rash and peripheral neuropathy are the first symptoms and are accompanied by Epstein-Barr virus (EBV) infection.